Research progress of gut microbiota and its metabolites in polycystic ovary syndrome - Qin, Shiyi; Guo, Shimeng; Tan, Xinmiao; Li, Ke; Huang, Jiayu (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) ranks among the most widespread endocrine and metabolic conditions affecting women of childbearing age, but its specific pathogenesis remains unknown. More and more evidence indicates that PCOS may be a complex polymorphic disease, influenced by epigenetic and environmental factors, including diet and lifestyle. This review focuses on the role of the gut microbiota and its metabolites in PCOS, a topic that has gained significant attention recently due to the established link between the gut microbiome and metabolic disorders.